2022
DOI: 10.1155/2022/3712500
|View full text |Cite
|
Sign up to set email alerts
|

An Energy Metabolism Study on the Efficacy of Naoxintong Capsules against Myocardial Infarction in a Rat Model

Abstract: Background. In myocardial ischemia, optimizing the myocardial metabolic phenotype to improve cardiac function is critical. Naoxintong capsules (NXT) are widely prescribed in Chinese medicine for the treatment of cerebrovascular and cardiovascular diseases. Methods. In this study, a rat model of myocardial infarction was established by ligation of the left anterior descending coronary artery. The structure and function of the heart were evaluated using echocardiography. The pathological changes of the rat myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The reasons for these changes, apart from excess ROS leading to increased GSH depletion in cardiomyocytes, are disturbances in the anabolic process of GSH, causing a further decrease in intracellular GSH content. Many preclinical studies have demonstrated that the expression of key enzymes for GSH synthesis (GCL, SLC7A11, GS) and GSSG reduction-related enzymes (G6PD, NADPH, and GR) is downregulated in myocardium exposed to pathological factors [40,[43][44][45][46][47][48][49][50]. However, enhanced expression of GGT and MRP1, which are associated with the γ-glutamyl cycle, has been observed in damaged myocardium [33,34,51,52].…”
Section: Metabolism Of Gshmentioning
confidence: 99%
“…The reasons for these changes, apart from excess ROS leading to increased GSH depletion in cardiomyocytes, are disturbances in the anabolic process of GSH, causing a further decrease in intracellular GSH content. Many preclinical studies have demonstrated that the expression of key enzymes for GSH synthesis (GCL, SLC7A11, GS) and GSSG reduction-related enzymes (G6PD, NADPH, and GR) is downregulated in myocardium exposed to pathological factors [40,[43][44][45][46][47][48][49][50]. However, enhanced expression of GGT and MRP1, which are associated with the γ-glutamyl cycle, has been observed in damaged myocardium [33,34,51,52].…”
Section: Metabolism Of Gshmentioning
confidence: 99%
“…In line with shifted metabolite profiles, mechanism studies indicated the effects of NXT in regulating metabolism associated crucial proteins, including silent information regulator 1 (SIRT1), peroxisome proliferator-activated receptor gamma coactivator 1α (PGC-1α), and a subunit of mitochondrial ATP synthase (ATP5D). These results together emphasized the cardioprotective effects of NXT against myocardial infarction, and highlighted the regulatory roles of NXT in energy metabolism related metabolic reprogramming ( Zhao et al, 2022 ). Activated platelets is another crucial risk factor for myocardial infarction occurrence.…”
Section: Pharmacological Propertiesmentioning
confidence: 72%
“…Liu et al (2022) used UPLC-IT-TOF-MS/MS to qualitatively analyze the metabolites of berberine in human hepatocellular carcinoma cells to elucidate the biodistribution and pharmacokinetic profile of berberine and its metabolites in hepatocytes. Zhao et al (2022) targeted analysis of 29 kinds of energy metabolites in myocardial tissue based on UPLC-QQ-MS, and verified that Naoxintong Capsules played a role in treating myocardial infarction by affecting part of energy metabolism.…”
Section: Pharmacodynamic Evaluationmentioning
confidence: 79%